Optimizing faba bean cultivation: assessing varietal performance in spring and fall - Torabian, Shahram; Zakeri, Hossein; Farhangi-Abriz, Salar (Frontiers in Agronomy, 2024)
The need to identify specialty crops in Virginia has driven interest in faba beans (Vicia faba L.), which offer potential benefits for crop rotation systems. As a cool-season crop, faba beans can be planted in both fall and spring, providing flexibility in farming schedules. A field study was conducted at Randolph Farm, the Virginia State University Research and Extension Farm, using a completely randomized factorial block design. This study examines the performance of seven faba bean varieties—Ethiopia, NEB247, Aprovecho, EN3, EN47, Windsor and EN45—across three spring (late February, late March and mid April), and three fall (late September, early October and late October) planting dates. Our results demonstrate that both variety and planting date significantly influence the yield and yield components of faba beans. Among the varieties tested, Windsor and EN47 exhibited superior traits across multiple categories, making them preferable for achieving high yields. Conversely, varieties such as EN45, Aprovecho, and NEB247 showed poor performance. Fall planting dates generally resulted in superior growth, yield, and maturity characteristics, underscoring their importance for maximizing faba bean production. We observed that faba beans planted in the fall had 58% more branches, 100% more shoot dry matter, 34% higher 100-seed weight, double the grain yields, and 8% higher harvest index compared to those planted in the spring. To further enhance faba bean production, additional studies are suggested to clarify the physiological relationships between photosynthesis rates and the sink-source dynamics. Furthermore, investigating how planting dates impact the nutrient components of faba beans will provide deeper insights into optimizing their cultivation.